INCREASING RECOMBINANT PENICILLIN G ACYLASE PRODUCTION: GENETIC, PROTEIN ENGINEERING, AND PRODUCTIVITY IMPROVEMENT - Is Helianti (BRIN - Badan Riset dan Inovasi Nasional, 2022)
B-lactam derived antibiotics are the most used globally for treatment against different infections caused by pathogenic bacteria and comprises 65% of the world antibiotics. Recently, penicillin G acylase (PGA) is used as biocatalyst for those B-lactam antibiotics production by which 6-aminopenicillanic acid (6-APA) or 7-aminodeacetoxycephalosporanic acid (7-ADCA) as the building blocks is produced. Commercialized PGA from native microbial resources are still limited to E. coli. Therefore, genetic engineering approach such as cloning and expression in other microbial hosts were assessed to enhance bacterial strains that produce PGA. However, such improvement could increase immature precursors accumulation and lowering the enzyme yield, activity, or stability. This review focus on the review of PGA recombinant produced by several microbial host, their expression levels, and improvement achieved by some modification such as replacement of signal peptide and promoter continued to protein engineering to utilize the enzymes in synthetizing amoxicillin rather than to hydrolyses Penicillin G.